Portable EMG Monitoring System for Hippotherapy - (:unkn) unknown (Institute of Electrical and Electronics Engineers Inc., 2019)
Hippotherapy is the use of horse riding for rehabilitation and therapeutic purpose, which has proven its efficiency in improving upper legs, lower back, trunk, and abdominal muscle strength. This project aims to design a portable system that monitors electrical activity generated by targeted muscles during hippotherapy and robotic hippotherapy sessions to provide therapists with a real-time evaluation. The system consists of two electromyography channels, a 5.0 TFT touch display, a microcontroller, and a boosted rechargeable Li-Po battery, with the appropriate basic electronic elements. The user interface is designed to be simple, easy to use, and it provides two different pieces information, each displayed on a separate page of the screen: The raw EMG signal from each channel as a function of time, and the average muscle activity level from each channel as a single gauge with two indicators. © 2019 IEEE.
Keywords: Biosignal monitoring system; electromyography; hippotherapy; muscle strength; Touch screen